Recyclable Oxofluorovanadate‐Catalyzed Formylation of Amines by Reductive Functionalization of CO2 with Hydrosilanes. Issue 7 (24th February 2021) - Wu, Shanxuan; Huang, Zijun; Jiang, Xiaolin; Yan, Fachao; Li, Yuehui; Du, Chen‐Xia
Abstract: An efficient method has been developed for the reductive amination of CO2 by using readily available and recyclable oxofluorovanadates as catalysts. Various amines are transformed into the desired N ‐formylated products in moderate to excellent yields at room temperature in the presence of phenylsilane. Mechanistic studies based on in situ infrared spectroscopy suggest a reaction pathway initiated through F−Si interactions. The activated phenylsilane allows for CO2 insertion to produce phenylsilyl formate, which undergoes attack by the amine to generate the target product. Abstract : Achievements in amination : Metal oxofluorovanadates, such as K2 VOF4, are found to be efficient catalysts for the reductive amination of carbon dioxide. The heterogeneous catalysts can be recycled by simple centrifugation and reused for four cycles without loss of activity.